Endodontic treatment failure caused by arsen utilization as the devitalization material - Sukartini, Endang; Darliana, Kurniasri (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
Root canal treatment diagnoses as pulpitis irreversible can be treated in a non-vital condition with devitalization material. Arsenic is one of devitalization material that used in inflammatory pulp tissue before it is going to endodontic treatment. The long-term use of it or the leak of using this arsenic can cause the toxic effect of the pulp tissue. The case is going to report is about the damage of gingival tissue and alveolar that caused by the uncarefullness using of arsenic. Inappropriate arsenic applications cause the leak that able to spread to gingival tissue and will become necrosis. Now a day, the using of arsenic begin to leave because of the toxicity sad effect. This report is going to report how much the damage using arsenic trioxide (As2O3) and the effort from the leakness.